Best Linear Methods of Approximation of Functions of the Hardy Class $H_p$ - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine the exact value of the best linear polynomial approximation of a unit ball of the Hardy space $H_p, 1 ≤ p ≤ ∞$, on concentric circles $Tρ = z ∈ C:|z|=ρ, 0 ≤ ρ < 1$, in the uniform metric. We construct the best linear method of approximation and prove the uniqueness of this method.